Oxford handbook of medical ethics and law - Herring, Jonathan; Smajdor, Anna; Wheeler, Robert (Consultant neonatal and pediatric surgeon) (Oxford handbooks, 2022)
"Doctors have been concerned with ethics since the earliest days of medical practice. Traditionally, medical practitioners have been expected to be motivated by a desire to help their patients. Ethical codes and systems, such as the Hippocratic Oath, have emphasised this. During the latter half of the 20th century, advances in medical science, in conjunction with social and political changes, meant that the accepted conventions of the doctor/patient relationship were increasingly being questioned. After the Nuremberg Trials, in which the crimes of Nazi doctors, among others, were ex-posed, it became clear that doctors cannot be assumed to be good simply by virtue of their profession. Not only this, but doctors who transgress moral boundaries can harm people in the most appalling ways"--